2008
DOI: 10.1177/0011128707308102
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Validity of a Gender-Responsive Needs Assessment

Abstract: Risk assessment and classification systems for women have been largely derived from male-based systems. As a result, many of the needs unique to women are not formally assessed or treated. Emerging research advocating a gender-responsive approach to the supervision and treatment of women offenders suggests that needs such as abuse, mental health, substance abuse, relationship difficulties, self-esteem, self-efficacy, and parenting issues are important treatment targets. Although these needs may be highly preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 89 publications
6
113
2
Order By: Relevance
“…In comparison, incarcerated men only reported a 2%-6% rate of sexual abuse (Bureau of Justice Statistics, 1999). Other studies have found the rate much higher, around 75%, which could be the consequence of underreporting (Owen & Bloom 1995;Salisbury et al 2009). The high discrepancy between men and women make this issue gender specific.…”
Section: Trauma and Abusementioning
confidence: 84%
See 4 more Smart Citations
“…In comparison, incarcerated men only reported a 2%-6% rate of sexual abuse (Bureau of Justice Statistics, 1999). Other studies have found the rate much higher, around 75%, which could be the consequence of underreporting (Owen & Bloom 1995;Salisbury et al 2009). The high discrepancy between men and women make this issue gender specific.…”
Section: Trauma and Abusementioning
confidence: 84%
“…Major mood disorders, such as those frequently seen with women, can be overlooked if they have not been previously diagnosed and recorded. (Salisbury et al 2009) Even though mood disorders have a significant impact on female recidivism, (Deschenes et al 2007), lack of attention is given to them during assessment. …”
Section: Mental Illnessmentioning
confidence: 99%
See 3 more Smart Citations